ACQUIRED HEMOPHILIA A IN 3 YEARS OLD CHILD IN LAMPUNG ETHNIC GROUP - Astrini, Nabila Putri (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
Acquired Hemophilia A is extremely rare in children. It is about 1:1,000,000 cases per year. Although it is rare, it can cause fatal condition to death. A boy, 3 years old, had a complaint of bruising on the face and extremities, the swelling often occur spontaneously, with no history of coagulation abnormality in family. Nonpharmacological management to patient was education about the patient’s condition and the kind of activities that should be limited. While the pharmacological management was transfusion of fresh frozen plasma, cryoprecipitate transfusion, and tranexamic acid injection, which were given for 6 days and responds well. Acquired hemophilia A must obtain adequate management immediately, both of nonpharmacologic and pharmacologic. [J Agromed Unila 2014; 1(3):253-256] Keyword: acquired hemophilia A, child, Lampung, treatment